HUBUNGAN PENGETAHUAN DAN PELAKSANAAN 3M PLUS DENGAN KEJADIAN DBD DI WILAYAH KERJA PUSKESMAS BASUKI RAHMAT KOTA BENGKULU - Santoso Ujang Effendi; Yusran Fauzi; Reni Satriani (Jurnal Sains Kesehatan, 2017)
This research was motivated by the high prevalence of  DHF incidence in  working area of Basuki Rahmat Public Health Center Bengkulu. This study aimed to determine the relationship between knowledge and implementation of 3M plus with incidence of DHF in working area of  Basuki Rahmat Public Health Center Bengkulu. This research was an Analytical Survey. This research used Case Control. The sample of this research was Family Head (KK) who lived in working area of Basuki Rahmat Public Health Center Bengkulu  with sample number 76 kk, consisted of 38 KK of case samples and 38 KK of control samples. Sampling technique was Total Sampling for case samples and Purposive Sampling for control samples. Data collection techniques were primary data and secondary data. Data analysis used was univariate analysis and bivariate analysis by using Chi-Square test (χ²) and to know the correlation of relationship used Contingency Coefficient (C) test. The results of this study showed: of  76 families, there were 38 KK (50.0%) whose family member had experienced DHF incidence, 32 KK (42.1%) had enough knowledge, 41 KK (53.9%) implemented 3M Plus, there was a significant relationship between knowledge with the DHF incidence with moderate relationship category, and there was a significant relationship between implementation of 3M Plus with the DHF incidence with medium relations category.Keywords: knowledge, 3M plus implementation, DHF incidence